Interleukin 1-beta (Il-1β) polymorphism and orthodontics: a systematic review - Juan Fernando Aristizábal; Héctor Ríos; Diego Rey; María Antonia Álvarez; Beatriz Parra-Patiño; Mario Ortiz (Universidad de Antioquia, 2019)
Introduction: the aim of this systematic review is to explore the published literature to analyze the relationship between polymorphism of interleukin 1-beta (IL-1β) and orthodontics. Methods: the search strategy developed for Medline, Scopus and Embase was used, verifying search records and selecting articles according to the guidelines set forth by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two researchers evaluated studies in humans undergoing orthodontic treatment that evaluate IL-1β polymorphism, movement speed and/or root resorption, including clinical trials, case-control studies, cross-sectional studies, and cohort studies, published up to April 2017. Results: of the 123 relevant articles identified, 9 studies published between 2001 and 2016 were included in the detailed analysis. Studies on tooth movement generally agree that there is an increase in IL-1β levels in the first hours after starting the orthodontic treatment. Conclusion: an association of IL-1β polymorphism with external root resorption and tooth movement speed was found.